2020
DOI: 10.1029/2020jc016616
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Interannual Sea Level Variability in the Western Tropical Pacific: Responses to El Niño and La Niña

Abstract: The western tropical Pacific (WTP) exhibits pronounced large-scale sea level anomalies (SLAs) during El Niño-Southern Oscillation (ENSO) events with amplitudes of~0.1 m, exerting potential threats to many low-lying islands. It is found that the sea level falling in El Niño condition is evidently stronger than the rising in La Niña condition. This SLA asymmetry in the WTP associated with ENSO is investigated in this study, and the underlying dynamic processes are explored. Such asymmetry is most prominent at ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 100 publications
(179 reference statements)
0
7
0
Order By: Relevance
“…El Niño events are broadly classified into eastern Pacific (EP) and central Pacific (CP) types with regard to spatial structure, although a mixed type has also been proposed to represent the events with flavors of both types (e.g., Ashok et al., 2007; Kao & Yu, 2009; Kug et al., 2009; Yu & Kim, 2013). Existing studies employed the composite analysis to identify the different impacts of two types of events (Chang et al., 2013; Q. Ren, Li, Zheng, et al., 2020; Shi et al., 2020) and revealed overall stronger signatures of EP events in the western Pacific (Hsin & Qiu, 2012; Tan & Zhou, 2018; X. Wang et al., 2020). However, the composite represents the common features of multiple events (Figure S1a in Supporting Information ) and is sometimes dictated by super events such as the 1997/1998 and 2015/2016 ones, particularly when event samples are few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El Niño events are broadly classified into eastern Pacific (EP) and central Pacific (CP) types with regard to spatial structure, although a mixed type has also been proposed to represent the events with flavors of both types (e.g., Ashok et al., 2007; Kao & Yu, 2009; Kug et al., 2009; Yu & Kim, 2013). Existing studies employed the composite analysis to identify the different impacts of two types of events (Chang et al., 2013; Q. Ren, Li, Zheng, et al., 2020; Shi et al., 2020) and revealed overall stronger signatures of EP events in the western Pacific (Hsin & Qiu, 2012; Tan & Zhou, 2018; X. Wang et al., 2020). However, the composite represents the common features of multiple events (Figure S1a in Supporting Information ) and is sometimes dictated by super events such as the 1997/1998 and 2015/2016 ones, particularly when event samples are few.…”
Section: Introductionmentioning
confidence: 99%
“…The Philippine Sea (PS) in the northwestern tropical Pacific Ocean is one of the regions with the strongest variability in sea level and upper‐layer circulation (Han et al., 2013, 2017; D. Hu et al., 2015; Qiu & Chen, 2012; Qiu et al., 2021), particularly on interannual timescales linked to the El Niño‐Southern Oscillation (ENSO). During the developing stage of El Niño events, the PS shows sea level falling in response to westerly wind bursts over the western Pacific, with the opposite changes occurring in La Niña condition (Chang et al., 2013; Deepa et al., 2021; Han et al., 2019; Li et al., 2012; Q. Ren, Li, Zheng, et al., 2020; Zhai & Hu, 2012). Super El Niño events such as the 1982/1983 and 1997/1998 ones gave rise to sea level falling near the western tropical Pacific islands by up to 20–30 cm, dramatically increasing the explosion risks of shallow coral reefs and damaging local ecosystems (e.g., Widlansky et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al. (2020) showed that the negative skewness of SSH anomalies in the western tropical Pacific is due to asymmetry in the spatial pattern of zonal wind stress anomalies. More specifically, westerly wind stress anomalies that force off‐equatorial upwelling Rossby waves during El Niño are located further to the east compared to easterly wind stress anomalies during La Niña.…”
Section: Introductionmentioning
confidence: 99%
“…They also pointed out that the magnitude of sea surface height (SSH) anomalies in the western tropical Pacific prior to the Ningaloo Niño is larger than that prior to the Ningaloo Niña. These asymmetries seem counterintuitive since it is known that El Niño, which often co-occurs with the Ningaloo Niña, is typically stronger than La Niña, which often co-occurs with the Ningaloo Niño (Ren et al, 2020;Su et al, 2010), that is, in the western tropical Pacific, negative SSH anomalies associated with El Niño are stronger than positive SSH anomalies associated with La Niña (Figure S1; Ren et al, 2020). Ren et al (2020) showed that the negative skewness of SSH anomalies in the western tropical Pacific is due to asymmetry in the spatial pattern of zonal wind stress anomalies.…”
mentioning
confidence: 99%
See 1 more Smart Citation